Temporal dynamics of microglia-astrocyte interaction in neuroprotective glial scar formation after intracerebral hemorrhage - Jingwei Zheng; Haijian Wu; Xiaoyu Wang; Guoqiang Zhang; Jia'nan Lu; Weilin Xu; Shenbin Xu; Yuanjian Fang; Anke Zhang; Anwen Shao; Sheng Chen; Zhen Zhao; et al. (Elsevier, 2023)
The role of glial scar after intracerebral hemorrhage (ICH) remains unclear. This study aimed to investigate whether microglia-astrocyte interaction affects glial scar formation and explore the specific function of glial scar. We used a pharmacologic approach to induce microglial depletion during different ICH stages and examine how ablating microglia affects astrocytic scar formation. Spatial transcriptomics (ST) analysis was performed to explore the potential ligand-receptor pair in the modulation of microglia-astrocyte interaction and to verify the functional changes of astrocytic scars at different periods. During the early stage, sustained microglial depletion induced disorganized astrocytic scar, enhanced neutrophil infiltration, and impaired tissue repair. ST analysis indicated that microglia-derived insulin like growth factor 1 (IGF1) modulated astrocytic scar formation via mechanistic target of rapamycin (mTOR) signaling activation. Moreover, repopulating microglia (RM) more strongly activated mTOR signaling, facilitating a more protective scar formation. The combination of IGF1 and osteopontin (OPN) was necessary and sufficient for RM function, rather than IGF1 or OPN alone. At the chronic stage of ICH, the overall net effect of astrocytic scar changed from protective to destructive and delayed microglial depletion could partly reverse this. The vital insight gleaned from our data is that sustained microglial depletion may not be a reasonable treatment strategy for early-stage ICH. Inversely, early-stage IGF1/OPN treatment combined with late-stage PLX3397 treatment is a promising therapeutic strategy. This prompts us to consider the complex temporal dynamics and overall net effect of microglia and astrocytes, and develop elaborate treatment strategies at precise time points after ICH.